STRATEGY OF FRENCH POLITENESS IN THE FILM "COMME UN CHEF": PRAGMATIC ANALYSIS - Mutmainnah; Andi Faisal; Gusnawaty (International Journal of Social Science, 2022)
This study aims to determine the linguistic politeness strategies and linguistic characteristics that include formal and informal greetings and language functions in Daniel Cohan's film "Comme un Chef". This study uses a qualitative descriptive research method with a pragmatic approach. The source of the data for this study is speech that adheres to linguistic politeness. This data collection uses the method of listening by systematically observing and recording. The theory used was Brown and Levinson's language politeness theory including four strategies, namely the bald-on record strategy, positive politeness strategy, negative politeness strategy, off-record politeness strategy and silent strategy. The results showed that positive politeness strategies were more dominantly used than other politeness strategies, namely frank politeness strategies, negative politeness strategies, vague politeness strategies, and silent politeness strategies. Positive politeness strategies are realized by giving or asking for reasons and giving gifts (sympathy or appreciation). Negative politeness strategies are realized by minimizing the burden of requests and giving respect. Politeness strategies are vaguely realized by using gestures. Furthermore, linguistic features related to politeness, namely non-formal greetings are more dominantly used when communicating. Then, the language functions that are more often found in each politeness strategy are conative, emotive and referential.